2006
DOI: 10.1038/sj.ki.5000133
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bile salt-dependent lipase, a 110 kDa pancreatic protein, in urines of healthy subjects

Abstract: Bile salt-dependent lipase (BSDL), a 110 kDa glycoprotein secreted by the pancreatic acinar cells, participates in the duodenal hydrolysis of dietary lipid esters. Recent in vitro and in vivo studies demonstrated that the BSDL reaches the blood via a transcytosis motion through enterocytes, suggesting that this enzyme may play a role in vascular biology. Once in the blood, BSDL should be eliminated. We address the hypothesis that BSDL may be filtered by the glomerulus and eliminated in urines. Immunological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…The glomerular filtration barrier for proteins has generally been considered to be in the range of albumin, which has a glomerular filtration fraction of Ͻ0.01 (21). However, we have shown that transferrin, 80 kD, is filtered to some extent normally both in human kidney and in rats and mice (22), and recently a 110-kD pancreatic lipase was found in the urine of healthy humans (23). These results support the observations of this study of a limited but significant glomerular filtration of recombinant ␣-Gal A in ␣-Gal A-deficient mice and patients, and this filtration is probably even more pronounced in patients with Fabry-Anderson disease and proteinuria.…”
Section: Discussionmentioning
confidence: 94%
“…The glomerular filtration barrier for proteins has generally been considered to be in the range of albumin, which has a glomerular filtration fraction of Ͻ0.01 (21). However, we have shown that transferrin, 80 kD, is filtered to some extent normally both in human kidney and in rats and mice (22), and recently a 110-kD pancreatic lipase was found in the urine of healthy humans (23). These results support the observations of this study of a limited but significant glomerular filtration of recombinant ␣-Gal A in ␣-Gal A-deficient mice and patients, and this filtration is probably even more pronounced in patients with Fabry-Anderson disease and proteinuria.…”
Section: Discussionmentioning
confidence: 94%
“…We propose to reassess the significance and usefulness of this assay. Although glomerular filtration of a 130-kDa-large protein is obviously questionable, transferrin (80 kDa) and even bile salt-dependent lipase (110 kDa) are filtered under normal conditions (22,23), and increased glomerular leakage will increase filtered levels. Because cathepsin B has a much lower molecular weight, and consequently a much higher filtration coefficient than N-acetyl-␤-glucosaminidase, we suggest that cathepsin B could be an alternative marker for tubular dysfunction in glomerular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic CEL is transported from the duodenum via enterocytes to the blood (7), where it associates with low density lipoprotein (8). The protein is cleared from the circulation by renal glomerulus filtration and can be detected in the urine of healthy individuals (9).…”
mentioning
confidence: 99%